Sistem Pendukung Keputusan Penilaian Kinerja Guru Menggunakan Metode Weighted Product di SMK Bakti Ilham Rancaekek - Miki Wijana; Gilang Juliansyah; Dheni Apriantsani Budiman (Jurnal Dimamu, 2022)
SMK Bakti Ilham Rancaekek is located on Jln. Peundeuy. No. 32, Bojongsalam, Kec. Rancaekek, Kab. Bandung 40394. Currently, the teacher performance assessment process is still relatively long due to the absence of a decision support system and the assessment process is still subjective because it does not refer to things that have nothing to do with teacher performance assessment in the learning process. The purpose of this research is to develop a system that can assist the school in the process of assessing the performance of teachers and students, peers and principals also participate in providing an assessment for teachers. The system was developed using the prototype method and system modeling designed using UML which includes use cases, activity diagrams and relationship tables. At the programming stage using the programming language PHP, CSS, HTML and MySQL as database management. The result of this thesis is a website-based teacher performance appraisal decision support system that can help schools to be faster and more efficient and objective.